Putting Social Development to Work for the Poor : An OED Review of World Bank Activities - Operations Evaluation Department (Washington, DC: World Bank, 2012)
This book finds that there is a strong positive association between including social development themes and project success. The Bank's social development resources are deployed in ways that are not optimally supportive of its social development goals, however. The study found that the Bank's mission and policy priorities related to social development receive uneven treatment across Regions, and gaps in skills and M&E lead to uneven treatment within countries. To improve development outcomes, the Bank needs to: 1) demonstrate the value of incorporating social development themes in its work to its own staff as well as its borrowers; 2) develop capacity to identify critically needed social knowledge and to facilitate its flow; 3) provide staff with consistent access to essential social information to build social development into project designs and ensure that social development concerns are addressed during implementation (this will likely involve making greater use of in-country capacity); 4) ensure that stated Bank or policy priorities receive adequate treatment across Regions and countries, and throughout the project cycle; and 5) identify, and promote integration within, thematic combinations that improve outcomes.